On the Performance and Security of Multiplication in GF(2N) - Jean-Luc Danger; Youssef El Housni; Adrien Facon; Cheikh T. Gueye; Sylvain Guilley; Sylvie Herbel; Ousmane Ndiaye; Edoardo Persichetti; Alexander Schaub (Cryptography, 2018)
Multiplications in G F ( 2 N ) can be securely optimized for cryptographic applications when the integer N is small and does not match machine words (i.e., N < 32 ). In this paper, we present a set of optimizations applied to DAGS, a code-based post-quantum cryptographic algorithm and one of the submissions to the National Institute of Standards and Technology’s (NIST) Post-Quantum Cryptography (PQC) standardization call.